A microemulsion preparation of nanoparticles of europium in silica with luminescence enhancement using silver - Ma, Zhi Ya (2009)
A facile one-pot microemulsion method has been developed for the synthesis of spherical silver core–silica shell (Ag@SiO(2)) nanoparticles with europium chelates doped in the shell through a silane agent. The method is significantly more straightforward than other extant methods. Measurements of the luminescent emissions from the Ag@SiO(2) nanoparticles, in comparison with control silica nanoparticles without silver cores, showed that the presence of the silver cores can increase the fluorescence intensity approximately 24-fold and decrease the luminescence lifetime. This enhancement offers a potential increase in overall particle detectability with increased fluorophore photostability.